Combining portable coagulometers with the Internet: A new model of warfarin anticoagulation in patients following mechanical heart valve replacement - Huang, Yu; Huang, Lei; Han, Zhen (Frontiers in Surgery, 2022)
Heart valve replacement, as a safe and effective treatment for severe valvular heart disease, can significantly improve hemodynamics in patients, although they require lifelong anticoagulant therapy afterward. Warfarin, a cheap and highly effective vitamin K antagonist, remains the only anticoagulant recommended for lifelong use following mechanical heart valve replacement. However, the effect of warfarin anticoagulant therapy is complicated by physiological differences between patients and non-compliance with treatment at different degrees. Today, effective management of warfarin therapy after heart valve replacement has become an important issue. Portable coagulometers and the emergence of the Internet have provided new opportunities for long-term management of anticoagulation therapy, but the safety and affordability of this approach remain to be fully evaluated. This paper reviews recent progress using portable coagulometers and the Internet in management of warfarin anticoagulation therapy following mechanical heart valve replacement, which offers opportunities for reducing complications during postoperative anticoagulation and for facilitating patient compliance during follow-up.